The constitutional case for legal regulation of illicit drugs in South Africa - Vieira, Marco-Alain (Department of Public Law, 2022)
The principal argument of this paper is that South Africa's current drug policy is unsound and unconstitutional. The legislative and policy framework is based on the prohibition of certain psychoactive substances deemed illicit and the criminalisation of their production, distribution and use, to wit: prohibition drug policy. This paper contends that prohibition drug policy is unsound on the grounds that it is utterly ineffective and vulgarly counterproductive. This is because prohibition drug policy fails to reduce the demand for, restrict the supply of or allay the harms associated with drugs. Furthermore, prohibition drug policy, in fact, greatly exacerbates drug-related harms for individuals and their communities. This is starkly exposed in the light of the devastating consequences pursuant to the drug war. In addition, this paper contends that prohibition drug policy, and the legislation that enacts it, the Drugs and Drug Trafficking Act, is unconstitutional. This, on the grounds that it unjustifiably violates the right to privacy, the right to freedom, and the right to human dignity. Moreover, the alternative drug policy of decriminalisation is a far less restrictive means of achieving the legitimate purpose of drug control in society. Lastly, this paper contends that prohibition drug policy ought to be replaced instead by the more effective, just and humane policy of the legal regulation of drugs. This, on the grounds that the South African constitutional dispensation compels a drug policy that takes a human rights-based, public health approach to drug control.